The effects of Astragalus membranaceus on oxygen consumption in the intestine - Li, Shao-Zhi (World J Gastroenterol, 1997)
AIM: To investigate the effects of Astragalus membranaceus (AM) on intestinal oxygen consumption both in vivo and in vitro. METHODS: The oxygen consumption of the intestine was measured using an arteriovenous (A-V) O(2) difference analyzer after treatment with AM in the intestinal lumen of ten healthy, anesthetized mongrel dogs. The effects of AM on the oxygen consumption of the intestinal mucosa in vitro were observed using constant volume manometers. RESULTS: The oxygen consumption of the intestine in vivo increased significantly (P < 0.05 or P < 0.01) after treatment with AM compared to the saline control. The oxygen consumption significantly increased after treatment with the 30% AM dilution and the 50% AM dilution compared to that of the 10% AM dilution (P < 0.05). There was no significant difference between the 30% AM dilution and the 50% AM dilution (P > 0.05). The effects of AM on oxygen consumption of the intestinal mucosa in vivo were similar to those in vivo. After treatment with the 5% AM dilution and the 1% AM dilution, the intestinal oxygen consumption increased compared to the control (Krebs Ringer phosphate buffer (KRPB)) (P < 0.05 and P < 0.01, respectively). There was no significant difference between treatment with the 10% AM dilution and the KRPB control (P > 0.05). CONCLUSION: AM improved the function of intestinal oxidative metabolism.